Possibility of using Landsat satellite recordings in visualization and detection of thermal islands in the area of the city Vinkovci - Petrinjak, Ivana; Kranjčić, Nikola; Rezo, Milan; Đurin, Bojan (2020)
All satellite data is generated as a record of electromagnetic radiation detected on the satellite sensor. The product of collecting information in remote explorations is a digital satellite record consisting of a pixel network representing the smallest surface that a particular sensor can collect, which is also a spatial resolution of the image. The position of each pixel is determined in the Cartesian coordinate system. To allow the ability to monitor climate change or mitigate the consequences of a natural disaster, the USGS has developed the Earth Explorer tool. USGS (US Geological Institute) provides science on natural hazards endangering life and existence; water, energy, minerals and other natural resources we rely on. This analysis will highlight the ability to use and monitor satellite imagery using the Earth Explorer browser. All satellite images are processed in QGIS. The spatial resolution of the satellite index (NDVI) as a quantitative measure of the state of the vegetation cover was tested on Landsat 8 images in the area of the city of Vinkovci. Highlighted natural disasters are thermal islands, and damage to the forest cover.
Bibliografija: 15 jed.
Summary.
Keywords: Landsat 8 -- USGS Earth Explorer; Termalni otoci -- Satelitske snimke -- Prirodne katastrofe -- Poplave; Vinkovci